Réponse à certaines critiques sur l’approche neurolinguistique (ANL) - Claude Germain (Recherches en didactique des langues et des cultures)
In 2022 appeared the first in a series of articles (Antier, 2022a, 2022b, 2023) indiscriminately criticizing in a scathing manner the authors of the neurolinguistic approach (NLA) as well as their promoters, in particular attacking my work on NLA (Germain, 2017). This article is intended as a personal reaction to these attacks. I will first deal with the unrestrained adherence of the author of this series of articles to the views of Roussel and Gaonac’h (2017) on the subject of the NLA on "double dissociation", on the question of the explicit/implicit opposition, and on the absence of novelty in the NLA. Then, I will address the origins and purposes of the NLA, after which I will examine the epistemological posture of the author. Finally, after showing his confusion of genres, I will bring out the idea that his anti-NLA position is explained not only by his blind adherence to the erroneous assertions of Roussel and Gaonac'h and by his ignorance of the results of numerous empirical research on the NLA, but also and above all by a personal conflict of interest (as one of the co-authors of a language textbook) which in no way justifies his defamatory remarks coated in insidious rhetoric. I will place clear emphasis on the accusations in the first article (2022a) published in Recherches en didactique des langues et des cultures.